Pengaruh Insentif, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada UMKM Di Kabupaten Bantul (Studi Kasus Pada UMKM di Kabupaten Bantul) - Gajali, Ahmad; Nugraeni, Nugraeni (Jurnal Media Informatika, 2024)
MSMEs have a very important role in the Indonesian economy, especially in Bantul Regency, Yogyakarta, where they are one of the main contributors to absorbing local employment energy. This shows the big role of MSMEs in reducing poverty levels and improving the welfare of local communities. In Bantul Regency, MSMEs may be the main employment providers. This may be due to the availability of natural and human resources, support from local governments, and the presence of a strong MSME community. The aim of this research is to highlight how incentives, motivation and work discipline impact employee performance in micro, small and medium enterprises (MSMEs) in Bantul Regency. Quantitative methods were used in this research. Primary data is in the form of questionnaires distributed to MSMEs in Bantul Regency, and secondary data is in the form of research processed by certain sources, articles, websites, etc. This research tested the hypothesis by collecting 50 respondents who met the requirements using multiple linear regression analysis as a sample. The results show that incentives have a positive and significant effect on the performance of MSME employees in Bantul, motivation has a positive and significant effect on the performance of MSME employees in Bantul, and work discipline has a positive and significant effect on the performance of MSME employees in Bantul. And finally, simultaneously, incentives, motivation and work discipline have a positive and significant effect on the performance of MSME employees in Bantul. is a brief summary of the article to help readers quickly ascertain the purpose of the research and in accordance with research needs. The abstract must be clear and informative, contain about the objectives, methods, and results of the research The length of the abstract is between 90 to 230 words. Avoid unusual abbreviations and define all symbols used in the abstract. Using keywords related to the recommended research topic.